Test of Cable Products in Respect of Thermal and Dynamic Stability - M. A. Korotkevich; I. V. Oleksiouk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers conditions for selection of  power supply of the unit which is used for testing samples of cable products by thermal and dynamic stability currents. It has been shown that while conducting testing by thermal and dynamic stability currents at nominal cable voltage it is more justifiable to use a percussive energy accumulator, and in the case when the voltage is low an inductive energy accumulator is used.